Pengembangan Objek Wisata Taman Bunga dalam Pemberdayaan Masyarakat Desa Jatimulyo Kecamatan Jati Agung Kabupaten Lampung Selatan Menurut Perspektif Ekonomi Islam - Muji Suwarno (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2022)
The flower garden in the Jati Agung District is one of the tourism assets based on local agro tourism, which is a flower display garden. With this flower garden tour, the Jatimulyo community can be independent without depending on others and can be an opportunity for the local community to help their economy. Therefore, assistance is needed in the form of developing science and technology for the trading community in that place. This type of research includes field research. This research will eventually be analyzed, so the research process raises data from problems in the field relating to the development of flower garden tourism objects in empowering the community of Jatimulyo village, Jati Agung sub-district, South Lampung district according to an Islamic economic perspective. Based on the results of the study, it is known that the impact of developing tourism potential on community economic empowerment in flower garden tourism is the independence of the community in developing self and regional potential for community and regional development. The economic empowerment of the community according to Islamic economics is as the goal of Islamic economics itself, namely all the rules revealed by Allah SWT in the Islamic system that lead to the achievement of goodness and prosperity. Therefore, a flower garden tourism object in a religious view is positive, because it is run in a good way to achieve a good goal as well. Therefore, suggestions that can be given are to the local government of Jatimulyo village and Jati Agung sub-district, it is hoped that they can continue to develop ideas or ideas for the development of tourism objects and can continue to socialize and invite local people to be aware of tourism and can participate in the development of tourism management that can improve tourism. community and regional welfare.